Trans-synaptic molecular context of NMDA receptor nanodomains - Michael C. Anderson; Poorna A. Dharmasri; Martina Damenti; Sarah R. Metzbower; Rozita Laghaei; Thomas A. Blanpied; Aaron D. Levy (Nature Communications)
Abstract Tight coordination of spatial relationships between protein complexes is required for cellular function. In neuronal synapses, proteins responsible for neurotransmission form subsynaptic nanoclusters whose trans-cellular alignment modulates synaptic signal propagation. However, the spatial relationships between these proteins and NMDA receptors (NMDARs), which are required for learning and memory, remain undefined. Here, we mapped key NMDAR subunits relative to active zone and post-synaptic density reference proteins using multiplexed super-resolution DNA-PAINT microscopy in rat hippocampal neurons. GluN2A and GluN2B subunits formed diverse nanoclusters that, surprisingly, were not localized near presynaptic vesicle release sites marked by Munc13-1. However, a subset of release sites was enriched with NMDARs, and modeling indicated this nanotopography promotes NMDAR activation. These enriched sites were internally denser with Munc13-1, aligned with PSD-95, and closely associated with specific NMDAR nanodomains. NMDAR activation rapidly reorganized this relationship, suggesting a structural mechanism for tuning NMDAR-mediated synaptic transmission. These findings suggest synaptic functional architecture depends on assembly of and trans-cellular spatial relationships between multiprotein nanodomains.